FOXO4-DRI improves spermatogenesis in aged mice through reducing senescence-associated secretory phenotype secretion from Leydig cells - Yanqing Li; Chi Zhang; Haicheng Cheng; LinYan Lv; Xinning Zhu; Menghui Ma; Zhenhan Xu; Junxian He; Yun Xie; Xing Yang; Xiaoyan Liang; Chunhua Deng; et al. (Experimental Gerontology, 2024)
Male ageing is always accompanied by decreased fertility. The forkhead O (FOXO) transcription factor FOXO4 is reported to be highly expressed in senescent cells. Upon activation, it binds p53 in the nucleus, preventing senescent cell apoptosis and maintaining senescent cells in situ. Leydig cells play key roles in assisting spermatogenesis. Leydig cell senescence leads to deterioration of the microenvironment of the testes and impairs spermatogenesis. In this study, we observed that FOXO4-DRI, a specific FOXO4- p53 binding blocker, induced apoptosis in senescent Leydig cells, reduced the secretion of certain Senescence-Associated Secretory Phenotype and improved the proliferation of cocultured GC-1 SPG cells. In naturally aged mice, FOXO4-DRI-treated aged mice exhibited increased sperm quality and improved spermatogenesis.